K+ Channels in Primary Afferents and Their Role in Nerve Injury-Induced Pain - Smith, Peter A. (Frontiers in Cellular Neuroscience, 2020)
Sensory abnormalities generated by nerve injury, peripheral neuropathy or disease are often expressed as neuropathic pain. This type of pain is frequently resistant to therapeutic intervention and may be intractable. Numerous studies have revealed the importance of enduring increases in primary afferent excitability and persistent spontaneous activity in the onset and maintenance of peripherally induced neuropathic pain. Some of this activity results from modulation, increased activity and /or expression of voltage-gated Na+ channels and hyperpolarization-activated cyclic nucleotide–gated (HCN) channels. K+ channels expressed in dorsal root ganglia (DRG) include delayed rectifiers (Kv1.1, 1.2), A-channels (Kv1.4, 3.3, 3.4, 4.1, 4.2, and 4.3), KCNQ or M-channels (Kv7.2, 7.3, 7.4, and 7.5), ATP-sensitive channels (KIR6.2), Ca2+-activated K+ channels (KCa1.1, 2.1, 2.2, 2.3, and 3.1), Na+-activated K+ channels (KCa4.1 and 4.2) and two pore domain leak channels (K2p; TWIK related channels). Function of all K+ channel types is reduced via a multiplicity of processes leading to altered expression and/or post-translational modification. This also increases excitability of DRG cell bodies and nociceptive free nerve endings, alters axonal conduction and increases neurotransmitter release from primary afferent terminals in the spinal dorsal horn. Correlation of these cellular changes with behavioral studies provides almost indisputable evidence for K+ channel dysfunction in the onset and maintenance of neuropathic pain. This idea is underlined by the observation that selective impairment of just one subtype of DRG K+ channel can produce signs of pain in vivo. Whilst it is established that various mediators, including cytokines and growth factors bring about injury-induced changes in DRG function and excitability, evidence presently available points to a seminal role for interleukin 1β (IL-1β) in control of K+ channel function. Despite the current state of knowledge, attempts to target K+ channels for therapeutic pain management have met with limited success. This situation may change with the advent of personalized medicine. Identification of specific sensory abnormalities and genetic profiling of individual patients may predict therapeutic benefit of K+ channel activators.